Active and Passive Realization of Fractance Device of Order 1/2 - B. T. Krishna; K. V. V. S. Reddy (Active and Passive Electronic Components)
Active and passive realization of Fractance device of order 1/2 is presented. The crucial point in the realization of fractance device is finding the rational approximation of its impedance function. In this paper, rational approximation is obtained by using continued fraction expansion. The rational approximation thus obtained is synthesized as a ladder network. The results obtained have shown considerable improvement over the previous techniques.